BETTER EFFICIENCIES OF SOLAR AIR HEATERS ACHIEVED WITH DIFFERENT AIRFLOWS - A BRIEF REVIEW - - VISARION-CATALIN IFRIM; TEODOR POP (Journal of Engineering Studies and Research)
The use of solar air heater systems brings with it the convenience of having hot air at discretion for heating households with quite low prices compared to the use of conventional heating sources. The researchers desire to achieve the highest thermal efficiency of these systems has led to the emergence of different ways of improvement. The present work is focused on the available literature in the field of SAH systems made with different types of air flow. The paper also presents the different designs for the realization of airflow types used by researchers for high efficiency during the years 2017-2021.